WNK4 is an Adipogenic Factor and Its Deletion Reduces Diet-Induced Obesity in Mice - Takahashi, Daiei (EBioMedicine, 2017)
The with-no-lysine kinase (WNK) 4 gene is a causative gene in pseudohypoaldosteronism type II. Although WNKs are widely expressed in the body, neither their metabolic functions nor their extrarenal role is clear. In this study, we found that WNK4 was expressed in mouse adipose tissue and 3T3-L1 adipocytes. In mouse primary preadipocytes and in 3T3-L1 adipocytes, WNK4 was markedly induced in the early phase of adipocyte differentiation. WNK4 expression preceded the expression of key transcriptional factors PPARγ and C/EBPα. WNK4-siRNA-transfected 3T3-L1 cells and human mesenchymal stem cells showed reduced expression of PPARγ and C/EBPα and lipid accumulation. WNK4 protein affected the DNA-binding ability of C/EBPβ and thereby reduced PPARγ expression. In the WNK4(−/−) mice, PPARγ and C/EBPα expression were decreased in adipose tissues, and the mice exhibited partial resistance to high-fat diet-induced adiposity. These data suggest that WNK4 may be a proadipogenic factor, and offer insights into the relationship between WNKs and energy metabolism.